Caring for a loved one with Alzheimer's an emotional journey - Geist, Mary Ellen; Doka, Kenneth J.; Coste, Joanne Koenig; Spatzeck-Olsen, Charity; Paraclete Video Productions; Paraclete Press (Brewster, MA : Distributed by Paraclete Press, 2012)
This dynamic video offers insight, hope, and understanding for anyone who cares for a loved one with Alzheimer's. This disease without cure currently afflicts more than 30 million people and there are no treatments to halt its progression, making caregiving both essential-and difficult.
Interviews: Mary Ellen Geist, Dr. Kenneth Doka, Joanne Koenig Coste.
DVD.
Keywords: Alzheimer's disease -- Patients -- Home care; Alzheimer's disease -- Patients -- Family relationships; Educational films; Nonfiction films; Popular works